The Use of Personal Pronoun in Political Discourse: A Case Study of the Final 2016 United States Presidential Election Debate - Kaewrungruang, Kunyaluck; Yaoharee, Ornkanya (rEFLections, 2018)
This study aims to investigate the use of personal pronouns in political speeches made by Donald Trump and Hilary Clinton in the 2016 US Presidential Election Debates. The focus is on uses of the first personal pronouns 'we' and 'I' as strategies to express persuasive messages and political ideologies especially the inclusion and exclusion of the participants’ 'self' and 'group’ reference. The data were selected from the TV broadcasted American Presidential Debate between Mr. Donald Trump and Mrs. Hillary Clinton on October 19, 2016. Textual and discourse analysis were adopted in order to examine in what context each first personal pronoun was used in the speeches. The findings reveal that the occurrences of the pronouns 'we' and 'I' in the speeches of both participants’ diﬀer and the uses of each pronoun in certain contexts also diﬀer significantly. The diﬀerent pronominal choices in diﬀerent contexts in the debates express diﬀerences in the persuasive strategies and political ideologies of the two candidates.